Application of Information Technology in SD Negeri 095196 Moho in Improving the Effectiveness of Online Learning - Siringoringo, Yan Batara Putra; Pasukat Sembiring; Asima Manurung; Enita Dewi Tarigan; Citra Dewi Hasibuan (Jurnal Pengabdian Pancasila (JPP), 2024)
In the world of education, the use of information technology (ICT), including multimedia technology, is very important to improve the quality of learning and ICT skills of teachers and students in facing the increasingly developing technological era, especially during the Covid-19 Pandemic, which requires learning to be carried out online. One of the ICT problems at SD Negeri 095196 Moho is that not all teachers optimize information technology by using existing computers. Existing computers are only used for administration, and school information systems have not been used effectively to manage online learning.